Late effects of childhood cancer treatment in long-term survivors diagnosed before the age of 3 years – A multicenter, nationwide study. (October 2022) - Latoch, Eryk; Zubowska, Małgorzata; Młynarski, Wojciech; Stachowicz-Stencel, Teresa; Stefanowicz, Joanna; Sławińska, Dorota; Kowalczyk, Jerzy; Skalska-Sadowska, Jolanta; Wachowiak, Jacek; Badowska, Wanda; Czajńska-Deptuła, Aneta; Dembowska-Bagińska, Bożenna; et al.
Abstract: Background: The effect of age on the incidence of late sequelae that occur after anticancer treatment in childhood is still not fully elucidated. In this multicenter study of long-term survivors diagnosed before age of three, we investigated the prevalence of late effects many years after treatment. Methods: The study group (n = 561) was selected from the Polish National Childhood Cancer Survivors Registry (n = 1761) created in 2007. A survivor was defined as an individual who has survived at least 5 years after completion of anticancer treatment. All children were diagnosed between 1991 and 2016, mean age at diagnosis was 1.82 years (range 0.03–2.99) and median follow up time - 9.85 years (range 5.0–23.6). They were treated in accordance with international protocols approved by the Polish Pediatric Leukemia and Lymphoma Group and Polish Solid Tumor Group. Chemotherapy alone was used in 192 (34.2%), chemotherapy and radiotherapy – 56 (10%), chemotherapy and surgery – 176 (31.4%), chemotherapy, radiotherapy, and surgery – 79 (14.1%), and surgery alone in 58 patients (10.3%). Results: Of all patients enrolled to the study, only 94 (16.8%) had normal function of all organs. Seventy-six (13.5%) children developed dysfunction in one organ, another 83 (14.8%) had symptoms or complaints suggestive of dysfunction in two organs or systems, 88 (15.7%) had abnormalities in three organs, and 220 (39.2%) had at least four or more dysfunctions. In the entire study group, dysfunctions most frequently (> 20% of cases) involved the following organs/systems: circulatory – 21.8%, urinary – 30.8%, gastrointestinal – 20.8%, immune – 23.5%, vision – 20.7%, hearing – 21.8%, and oral and masticatory dysfunction – 26.9%. We did not find any significant differences in organ dysfunction between children diagnosed under the age of 1 and those diagnosed at the age of 1–3, except for a lower incidence of thyroid abnormalities (p = 0.007) and the higher prevalence of liver dysfunction in youngest patients. In the subset with longer follow-up period (> 10 years) more frequent thyroid abnormalities (p = 0.019), male (p = 0.002) and female (p = 0.026) gonads dysfunction, as well as musculoskeletal problems (p < 0.001) were observed. Among subjects who received radiotherapy compared to those who did not, short stature (p = 0.001), and dysfunction of the following systems/organs – circulatory (p = 0.049), urinary (p = 0.012), thyroid gland (p < 0.0001), nervous (p = 0.007), immunological (p = 0.002), liver (p = 0.03), dental or chewing difficulties (p = 0.001), hearing (p = 0.001) and musculoskeletal (p = 0.026) were more frequently reported. When multimodal therapy was applied (chemotherapy, radiotherapy, and surgery) a higher incidence of short stature (p = 0.007), urinary system disorders (p < 0.0001), thyroid dysfunction (p < 0.0001), hearing loss (p < 0.0001), and skin problems (p = 0.031) were observed. Conclusion: This study confirms that radiotherapy and some specific toxicity of cytostatics are the most important factors affecting organ function. Apart from a higher incidence of liver dysfunction in the youngest patients, there were no significant differences in organ and system toxicities between children diagnosed under the age of 1 and those diagnosed at the age of 1–3. We have shown that this group requires systematic, careful and long-term follow-up.